Assessing sustainability and adaptive capacity in Arctic tourism - Dannevig, Halvor; Hovelsrud, Grete K; Dale, Ragnhild F; Rusdal, Tone; Olsen, Julia; Steenholt, Naja C.; Bjørst, Lill R.; James, Laura; Nilsson, Annika (Zenodo, 2021)
The shrinking Arctic sea ice is enabling an increase in Arctic cruise tourism opportunities Simultaneously Arctic tourism is increasing as a response of increased demand. Tourism is also a driver of change in the Arctic coupled socio-ecological system, inflicting changes on communities and local environments. This paper presents a framework for assessing local sustainability and resilience of tourism in fjord systems in Svalbard and Greenland. By co-production of salient impact categories of environmental and climate change in collaborations with marine biologists, oceanographers, social scientists and industry stakeholders, projections for these changes will be developed and subsequently used for co-development of sustainability indicators for tourism. The environmental change projections will also be used as input to participatory scenario workshops, which again enables social learning across different stakeholder groups, promoting community-owned solutions, and facilitating the sharing of experiences in a creative and collaborative way. Finally, we will co-develop adaptive co-management strategies for a sustainable and resilient tourism system in the Arctic.